Comparison of the pulsed call repertoires of killer whales (Orcinus orca) in Iceland and Norway - Anna Selbmann 1985- (2019)
Killer whale (Orcinus orca) pulsed call repertoires can provide information on the relatedness of groups and populations. Killer whales in Iceland and Norway are presumed to belong to the same ecotype and to have been in contact prior to the collapse of the Atlanto- Scandian herring stock in the 1960s but the actual level of contact between the two populations is unknown. Using data collected between 2005 and 2016 this study provides a detailed description of the call repertoire of killer whales in Iceland and updates existing catalogues of the Norwegian population. 42 call types and 30 subtypes are described in Iceland and 32 call types and 21 subtypes in Norway. Measurements of time and frequency parameters of 5752 calls (nIceland = 4,037, nNorway = 1,715) showed significant differences for most parameters but a high overlap between the populations. A discriminant function analysis classified 57% of calls correctly, thus performing only slightly better than a by- chance classification. However, a visual and aural comparison of all call types did not yield any matches between Icelandic and Norwegian calls, indicating the two populations have different call repertoires. This stands in contrast with expectations of similarities in the repertoires due to the presumed past contact between the populations. The consistent difference in repertoires suggests that if the populations have been in contact before they were likely not one totally mixed population. Efnisskrár háhyrninga (Orcinus orca) af taktslagsköllum geta veitt upplýsingar um skyldleika hópa og stofna. Íslenskir og norskir háhyrningar eru taldir tilheyra sama afbrigði háhyrninga og eru taldir hafa verið í samskiptum fyrir hrun norsk-íslenska síldarstofnsins á sjöunda áratugnum. Umfang samskipta á milli stofnanna tveggja er þó óþekkt. Hér er lögð fram nákvæm lýsing á kallaefnisskrám háhyrninga við Ísland og jafnframt er endurskoðuð skrá um köll hjá norska stofninum, byggð á gögnum sem safnað var á árunum frá 2005 til 2016. Alls var lýst köllum af 42 ...